The Optical Extinction Law Depends on Magnetic Field Orientation: The RV–ψ Relation - Brandon S. Hensley (The Astrophysical Journal)
For aspherical interstellar dust grains aligned with their short axes preferentially parallel to the local magnetic field, the amount of extinction per grain is larger when the magnetic field is along the line of sight and smaller when in the plane of the sky. To the extent that optical extinction arises from both aligned and unaligned grain populations with different extinction properties, changes in the magnetic field orientation induce changes in its wavelength dependence, parameterized by R _V  ≡  A _V / E ( B  −  V ). We demonstrate that the measured total and polarized extinction curves of the diffuse Galactic interstellar medium imply R _V varies from 3.21 when the magnetic field is along the line of sight ( ψ  = 0) to R _V  = 3.05 when in the plane of the sky ( ψ  = 90°). This effect could therefore account for much of the large-scale R _V variation observed across the sky ( σ ( R _V ) ≃ 0.2), particularly at high Galactic latitudes.